Outcome of community based planned intervention targeting perceptions, attitudes and health seeking behaviour regarding cancers in New Delhi, India - Kotwal, Atul; Seth, Tulika; Thakur, Rakesh; Rath, G. K.; Sharma, D. N.; Nagpal, Jitendra (International Journal Of Community Medicine And Public Health, 2020)
Background: Cancer prevention and control needs to be based on effective implementation of all approaches. Community as well as individual level interventions to increase knowledge and early reporting have shown effectiveness. A community-based intervention trial was conducted to design, implement and test short-term outcomes of evidence based preventive strategies. Methods: A mixed methods, three phased study was conducted in three districts of Delhi, which were selected by a random process. Two randomly selected districts out of these three were intervention districts while third was the control. A total sample of 500 in each district was studied in quantitative pre and post -intervention phases. Multistage, stratified, cluster sampling was utilized. Pre-tested and validated tools were used. Results: Post intervention, statistically significant higher scores were observed in all domains in intervention districts as compared to control (p<0.01). Though comparison of slum versus non-slum showed significant increment in knowledge and practice scores, with higher scores for non-slum respondents, the attitudes were very similar (p>0.05). The increment score changes between males and females was similar in all classes of society versus control district. Comparison within the intervention and control groups revealed increased scores in intervention districts and decreased scores in control district, in all domains (p<0.05). Conclusions: Our study has helped in understanding the determinants of perceptions, attitude and practices regarding cancer in the community, This, helped in formulating the need-based intervention strategies. Testing the short-term outcome of intervention showed it to be effective.